Agile Digital Learning, A New Paradigm in Education - Popa, Doinița (Didactica Danubiensis, 2024)
Agile learning represents a significant shift in educational methodologies, adapting to the needs and expectations of students in our fast-paced, technology-driven world. This approach is characterized by adaptability and collaboration and focuses on personalized learning experiences, which are increasingly essential, and traditional educational methodologies need to be more effective in the face of constant change. Agile learning in education is exceptionally flexible and student-centered, allowing educators to adapt their teaching methods to better meet the individual needs of students.